Turbulence-resistant high speed free-space optical communications using MUTC photodiodes - Beibei Cui; Shanyong Cai; Liqian Wang; Zhiguo Zhang (Results in Optics)
In free-space optical (FSO) communication systems, atmospheric turbulence induces scintillation of received optical power. Higher transmission optical power can compensate turbulence-induced scintillation and other channel attenuation. However, elevated optical power risks overloading the traditional positive-intrinsic-negative photodiode (PIN PD), as the peak of fluctuating optical power may surpass its saturation limit. Due to its extended input optical power range and wider bandwidth, the modified uni-traveling carrier (MUTC) PD emerges as a preferable alternative of PIN PD. The bit error rate (BER) of MUTC PD and PIN PD based FSO systems are numerically calculated, with both systems employing intensity modulation/direct detection (IM/DD) and pilot-assisted self-coherent detection. Simulation results show that the BER of MUTC PD system is reduced by up to 31.4 dB compared to the PIN PD system in 50 Gbps 10km FSO links.